The Influence of Workplace Facilities and Compensation on Job Satisfaction of Village Officials in Gembira Village, Gaung District, Indragiri Hilir Regency - Syamsir, Syamsir; Kurniawan , Very; Sari, Silvia (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to determine the influence of workplace facilities and compensation on the job satisfaction of village officials in Gembira Village, Gaung District, Indragiri Hilir Regency. Methodology/approach – A survey method was employed, with questionnaires distributed to village officials holding various positions within the Gembira Village administration. The collected data were analyzed using multiple linear regression techniques. Findings – The results indicate that workplace facilities and compensation significantly influence the job satisfaction of village officials. The workplace facilities variable positively contributes to job satisfaction, suggesting that improving workplace facilities can enhance job satisfaction. Similarly, the compensation variable demonstrates that fair and adequate compensation can increase job satisfaction among village officials. Novelty/value – This study highlights the importance of workplace facilities and compensation as key factors influencing job satisfaction among village officials. Effective management of these aspects within the village officials’ work environment can help improve their performance and loyalty to the organization.